A graça de Deus em suas mãos: análise dos elementos argumentativos e prosódicos no discurso religioso neopentecostal de R. R. Soares - Rodrigues, Ana Fabíola Camargo Fanton (2009)
This dissertation aims at analyzing the prosodic and argumentative elements that influence the constitution of persuasion in the religious preach of the church Igreja Internacional da Graça de Deus. Our main proposal is to provide a linguistic analysis of the sermon ―The Words‖ conducted by the missionary R.R.Soares and broadcast both on Bandeirantes and Rede TV television networks at prime time. It is possible to state that the general objectives are the ones of measuring if the argumentative and prosodic resources are shown with the same influence within the sermon, or if there is any of them that protrudes so that the general audience is more easily influenced. The central hyphotesis of this work is based on questioning the corroboration of prosody in argumentation. In order to fulfill it, we aimed at analyzing the corpus through a social historical contextualization, by showing some social cultural aspects of the neopentecostal religious phenomenon in the current Brazilian society, as well as the Theology of Prosperity inserted in this discourse. Next, we presented an analysis of the argumentation resources and the dimensions of their intervention in the religious preach and also the influence of Prosody. Finally, there is an analytical chapter which verified the way all these elements are shown in the corpus. We have concluded that, in the discourse studied – ―Religious Preach‖ –, prosody corroborates argumentation. Performed in association with the argumentative resources, prosody influences and benefits the constitution of the meaning in the text and also contributes to the effectiveness of persuasion.